(untitled) (Studia theodisca, 2012)
Although the Fleißer-Forschung has always emphasized the link between Marieluise Fleißer and the strong personalities she worked with in the Weimar period, little attention has been paid to her active role as a playwright. This paper aims to demonstrate the original value of Fleißer’s artistic project by adopting Pierre Bourdieu’s theory of cultural production. The analysis of Fleißer’s “position-takings” in the Ingolstädter Stücke unravels the personal viewpoint from which her aesthetic choices are defined, as well as the “differential signification” of her poetics within the literary field.